umm how did you get the two first expressions? i don't understand

Equation of a straight line passing through the origin is given by

y = mx, or y - mx = 0. If m1 and m2 are the slopes of a pair of straight lines, the combined equation is given by

\(\displaystyle (y - m_1x)(y-m_2x) = 0\)

\(\displaystyle y^2 - (m_1+m_2)x + m_1m_2x^2 = 0\)

Compare this equation with equation given in the problem. You can see that

\(\displaystyle m_1 + m_2 = -\frac{2h}{b}\)

and \(\displaystyle m_1m_2 = \frac{a}{b}\)